2015
DOI: 10.1111/jfbc.12172
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Chemical Constituents and Antioxidant Activity in Yellow Himalayan (R ubus ellipticus  Smith) and Hill Raspberry (R ubus niveus  Thunb.)

Abstract: Phytochemicals and antioxidant activity in the fruits of Rubus ellipticus and Rubus niveus were studied. A significant variation (P < 0.05) in total phenolics, flavonoids, monomeric anthocyanins, ascorbic acid and β-carotene content among genotypes of R. ellipticus was observed. Total phenolics ranged from 2.56 to 3.28 mg gallic acid equivalent (GAE)/gram (g) fresh weight (fw) for R. ellipticus and 3.21 mg GAE/g fw for R. niveus. Gallic acid, catechin, chlorogenic acid and caffeic acid were the major phenolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 32 publications
(40 reference statements)
4
24
3
Order By: Relevance
“…The mean activity observed in ABTS assay was 1.47 mM AAE /100 g dw. These results are in agreement with that in Hedychium spicatum and Valeriana jatamansi where ABTS values were significantly higher than the DPPH values using same method (Rawat et al 2011;Badhani et al 2015). The average value in DPPH assay was 0.75 mM AAE/100 g dw.…”
Section: Antioxidant Capacitysupporting
confidence: 90%
See 3 more Smart Citations
“…The mean activity observed in ABTS assay was 1.47 mM AAE /100 g dw. These results are in agreement with that in Hedychium spicatum and Valeriana jatamansi where ABTS values were significantly higher than the DPPH values using same method (Rawat et al 2011;Badhani et al 2015). The average value in DPPH assay was 0.75 mM AAE/100 g dw.…”
Section: Antioxidant Capacitysupporting
confidence: 90%
“…Previously, total phenolic and flavonoid content were found to be 7.10 6 0.11 and 6.10 6 0.05% in methanolic extract of the species, which is higher than the present study (Mishra et al 2015). Variation in these constituents can be used for breeding programmes as the success of any breeding program depends on identifying the genetic variation of traits and knowledge of the impact of environmental parameters on their expression (Badhani et al 2015). While analysing the phenolic content in different habitat types, populations growing under oak-mix forest (2.98 mg GAE/g dw) and open grassy land (2.99 mg GAE/g dw) showed comparatively higher total phenolic content than oak and pine forest (Fig.…”
Section: Results and Discussion Total Phenolic And Flavonoid Contentcontrasting
confidence: 58%
See 2 more Smart Citations
“…6 Studies have suggested that fruits are rich source of phenolics, flavonoids, tannins, anthocyanins, vitamins and antioxidants, and their regular consumption associated with reducing the risk of cancer, cardiovascular syndrome, aging and neurodegenerative diseases. 7,8 Gaultheria trichophylla Royle (family-Ericaceae), a high value wild edible plant, is decumbent, mat-forming aromatic shrub in higher altitude zone around 3200-5300 m asl. Species is widely distributed across the Trans Himalayan zones of India, China, Nepal, and Pakistan.…”
Section: Introductionmentioning
confidence: 99%